Glutathione peroxidase-like functions of 1, 2-diselenane-4, 5-diol and its amphiphilic derivatives: Switchable catalytic cycles depending on peroxide substrates. (1st January 2021) - Arai, Kenta; Sato, Yuumi; Nakajima, Ikumi; Saito, Manami; Sasaki, Moeka; Kanamori, Akiko; Iwaoka, Michio
Graphical abstract: Abstract: Amphiphilic derivatives of (±)- trans -1, 2-diselenane-4, 5-diol (DST ox ) decorated with long alkyl chains or aromatic substituents via ester linkages were applied as glutathione peroxidase (GPx)-like catalysts. The reduction of H2 O2 with the diselenide catalysts was accelerated through a GPx-like catalytic cycle, in which the diselenide (Se–Se) bond was reduced to the diselenolate form ([Se -, Se - ]) by coexisting dithiothreitol, and the generated highly active [Se -, Se - ] subsequently reduced H2 O2 to H2 O retrieving the original Se–Se form. In the lipid peroxidation of lecithin/cholesterol liposomes induced by 2, 2′-azobis(2-amidinopropane) dihydrochloride (AAPH), on the other hand, the Se–Se form directly reduced lipid peroxide (LOOH) to the corresponding alcohol (LOH), inhibiting the radical chain reaction, to exert the antioxidative effect. Thus, the two GPx-like catalytic cycles can be switched depending on the peroxide substrates. Furthermore, hydrophilic compounds with no or short alkyl groups (C3) showed high antioxidative activities for the catalytic reduction of H2 O2, while lipophilic compounds with long alkyl chains (C6-C14) or aromatic substituents were more effective antioxidants against lipid peroxidation. In addition, these compounds showed low cytotoxicity in cultured HeLa cells and exhibited sufficient anti-lipid peroxidative activities, suggesting their potentials as selenium-based antioxidative drugs.